South African Defence Procurement: Challenges and Developments Thirty Years after Democracy - Ernst Heydenrych (Scientia Militaria - South African Journal of Military Studies, 2025)
Research on South African public procurement is common, but defence procurement has received limited attention so far, despite its significant financial and operational impact. This is concerning considering the substantial discretion granted to defence-contracting authorities, and the ongoing issues of fraud, corruption, and tender irregularities within the Department of Defence and the South African National Defence Force. Given the constitutional requirement for public procurement to be fair, transparent, and cost-effective, there is a need for increased focus on the regulation of defence procurement. Accordingly, this article distinguishes between “acquisition” and “procurement” as the two forms of defence procurement in South Africa; identifies key challenges, such as the continued reduction in the defence budget by government; cost containment, project delays, and corruption; and reflects on the effect of the new Public Procurement Act (No. 28 of 2024). The article also offers recommendations for addressing these challenges and improving the defence procurement system, thus ensuring adherence to fairness, transparency, and efficiency. The research findings emphasised the importance of effective policy implementation to combat fraud and corruption, improve capacity, and align procurement practices with legal requirements; thus, enhancing the overall effectiveness of the South African defence procurement system.